TEAMS GAMES TOURNAMENT (TGT): IMPROVE MOTIVATION OF STUDYING SOCIAL STUDY ELEMENTARY SCHOOL STUDENTS - Dewi Rakhmawati (Universitas Sebelas Maret, 2018)
This research aims to describe Teams Games Tournament (TGT) to improve motivation of studying social students grade VI SD Negeri Kota Gede 5. Increase the motivation of studying IPS imposes on the results of the study. This research includes class action research model Kemmis and Mc Taggart. The subject in this study are students of class VI SD Negeri Kota Gede 2017-2018 Lesson 5 years. The number of students there are 30 consisting of self-11 male students and female students. The success of researchers this action is marked by changes in the direction of the improvement that is 80% of students have a very high level of motivation. The results showed that an increase in the learning motivation of students who reach the very high category from 60% to 90%. The results of the study, IPS also experienced an increase based on the number of students who achieved the KKM of 9 students to 22 students.